The Lima regional clubs seen as elements of conservationand diffusion of national folklore for tourism consumption - Olivera Alegre, Gloria (2017)
Lima has long been a city of Cusco and step towards Machu Picchu, you will not recognize enough attractions apart from the Historic Center of Lima, able to retain the international tourist few days in this city. This paper has tried to delve into the possibility of interest that has remained dormant for decades but the margin of involvement with the industry. The migrant when forced to live in Lima population saw as a social channel to the association of fellow countrymen which resulted in departmental, provincial and district emergency clubs. These clubs became an existential support but also in a «box» to preserve regional culture rural folk. These traditions could be a new product of recreational and cultural attractions that may have a claim.